2013
DOI: 10.1002/chem.201203050
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Reactions of Cationic Vanadium‐Phosphorus Oxide Clusters with C2Hx (x=4, 6): A DFT‐Based Analysis of Reactivity Patterns

Abstract: The reactivities of the adamantane-like heteronuclear vanadium-phosphorus oxygen cluster ions [VxP4−xO10].+ (x=0, 2–4) towards hydrocarbons strongly depend on the V/P ratio of the clusters. Possible mechanisms for the gas-phase reactions of these heteronuclear cations with ethene and ethane have been elucidated by means of DFT-based calculations; homolytic C–H bond activation constitutes the initial step, and for all systems the P–O. unit of the clusters serves as the reactive site. More complex oxidation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
8

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 122 publications
4
33
1
8
Order By: Relevance
“…TheODH process is completed by yet another hydrogen-atom migration from the terminal CH 2 unit to the adjacent V=Os ite,t hus generating 20,f rom which C 2 H 2 can be liberated. [81] For [V 4 O 10 ]C + ,O AT is kinetically and thermodynamically clearly favored;the same holds true for the HATpathway in the case of [P 4 O 10 ]C + .The branching ratio of OATversus HAT/ODH is mainly determined by the relative energies of the barriers TS 13/14 versus TS 13/16 in Figure 15, respectively.F or example,t he OATt ransition structure TS 13/14 is energetically lowest for the [V 4 O 10 ]C + /C 2 H 4 couple and increases upon Figure 14. [100] Ther eactivity patterns observed in the reactions of the well-studied homonuclear clusters [V 4 O 10 ]C + and [P 4 O 10 ]C + with C 2 H 4 are consistent with the calculated PESs.…”
Section: H Schwarzmentioning
confidence: 75%
See 2 more Smart Citations
“…TheODH process is completed by yet another hydrogen-atom migration from the terminal CH 2 unit to the adjacent V=Os ite,t hus generating 20,f rom which C 2 H 2 can be liberated. [81] For [V 4 O 10 ]C + ,O AT is kinetically and thermodynamically clearly favored;the same holds true for the HATpathway in the case of [P 4 O 10 ]C + .The branching ratio of OATversus HAT/ODH is mainly determined by the relative energies of the barriers TS 13/14 versus TS 13/16 in Figure 15, respectively.F or example,t he OATt ransition structure TS 13/14 is energetically lowest for the [V 4 O 10 ]C + /C 2 H 4 couple and increases upon Figure 14. [100] Ther eactivity patterns observed in the reactions of the well-studied homonuclear clusters [V 4 O 10 ]C + and [P 4 O 10 ]C + with C 2 H 4 are consistent with the calculated PESs.…”
Section: H Schwarzmentioning
confidence: 75%
“…[97] With regard to heteronuclear clusters, for example,[ V 4Àn P n O 10 ]C + , [80] [(V 2 O 5 ) n (SiO 2 ) m ] +/À (n = 1, 2; m = 1-4), [98] or [V n Al m O o ] +/À (n + m = 2, 3, 4; o = 3-10), [99] they all possess ah igh spin density located at at erminal oxygen atom that is not bound to the transition metal vanadium but to the main-group atom, that is AlÀO t C,S i À O t C,o rP ÀO t C.T he V=O t unit is completely inert. [68,96] However,a s shown in Table 1, an entirely different scenario is encountered when these cluster ions react with C 2 H x (x = 4, 6), [81,[100][101][102] and the major questions raised by the unexpected branching ratios can be summarized as follows: 1) What are the reasonable reaction mechanisms for these VPO clusters when subjected to these substrates? Common to the thermal reactions of all [V n P 4Àn O 10 ]C + clusters with CH 4 is af acile scission of the CÀHb ond with efficiencies of more than 60 %r elative to the collision rate.…”
Section: Structural Effects On Hydrogen-atom Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The exiting channels of these reactions were mainly hydrogen (H 2 ) elimination [50][51][52], ethylene elimination [32,50,51,[53][54][55][56][57][58], hydrogen-atom abstraction (HAA) [51,53,57,[59][60][61][62], oxygen-atom transfer (OAT) [50,53,55,56], and acetaldehyde formation [50,53]. Only the reaction with CrO 2 + [50] was reported to generate the free H atom, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 93%
“…[128][129][130][131][132][133][134][135] Zheng et al reported the photoelectron spectroscopy of MAlO x and M x AlO 2 -(M = Ti or V; x = 1, 2, or 3) BONCs. 65,125 Studies of BONC ions are becom-ing increasingly widespread: e.g., AuNbO 3 [138][139][140] and AlYO 3 + . 89,141 All the above systems are charged BONCs.…”
Section: Introductionmentioning
confidence: 99%